New Insights into the Pathogenesis and Therapies of IgA Nephropathy - Suzuki, Hitoshi; Novak, Jan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide and a frequent cause of kidney failure. Better understanding of the pathogenesis of IgAN and the related genetic, immunological, and cellular susceptibility factors are needed to enable the development of effective disease-specific therapy. This book brings together international experts to provide clinical and experimental studies and reviews with an emphasis on early diagnosis, prognosis, disease pathogenesis, determination of disease activity, and new strategies for treatment for IgAN.